1993
DOI: 10.1103/physrevlett.70.3603
|View full text |Cite
|
Sign up to set email alerts
|

Sticking, adsorption, and absorption of atomic H on Cu(110)

Abstract: The sticking coefficient of atomic hydrogen at T G = 1815 K on a Cu(l 10) surface has been determined to be 18%. In addition to the buildup of a chemisorption layer the absorption of atomic H into subsurface sites is observed. The subsurface sites are thermally less stable than the chemisorption sites. Model calculations for the phononic energy transfer and estimates for the parallel momentum transfer as well as for electron-hole pair excitation indicate that the first two mechanisms dominate the accommodation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 28 publications
3
26
0
1
Order By: Relevance
“…44 In the case of H/Si, theoretical investigations indicate that the diffusion 19,28,32 and desorption barriers 18 decrease substantially when the Si atoms relax. However, a model involving static lattice distortion of silicon between the two ''hydrogen-adsorbed'' and ''hydrogen-desorbed'' states, and a corresponding barrier change, would lead to a violation of detailed balance.…”
Section: Introductionmentioning
confidence: 99%
“…44 In the case of H/Si, theoretical investigations indicate that the diffusion 19,28,32 and desorption barriers 18 decrease substantially when the Si atoms relax. However, a model involving static lattice distortion of silicon between the two ''hydrogen-adsorbed'' and ''hydrogen-desorbed'' states, and a corresponding barrier change, would lead to a violation of detailed balance.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous work, which has addressed a range of systems, has suggested that T-ehp coupling makes a negligible or minor contribution for the specific processes and systems investigated, 18,34,35 which included H-atoms interacting with Cu(110). 36 Other previous work, 37 some of which also focused on H-atoms interacting with metal surfaces, 38,39 suggested that ehp excitation should constitute the dominant energy loss mechanism.…”
Section: Introductionmentioning
confidence: 98%
“…Bisschler et al used a soft cube model to investigate sticking, adsorption, and absorption of H-atoms on Cu(110). 36 Hammer and co-workers 41 used a potential energy surface (PES) based on semi-empirical effective medium theory and DFT calculations to study scattering of H-atoms from Cu(111) for incidence energies (E i ) ranging up to 1.2 eV and T s up to 500 K. An important conclusion from their work was that the surface corrugation needs to be taken into account: the Baule-model fails at predicting sticking probabilities, which are affected by energy conversion from normal to parallel translational motion, and by the possibility that the H-atoms penetrate the surface even at low E i . Klamroth and Saalfrank used reduced dimensionality quantum dynamical models, mixed-quantum classical models, and the classical trajectory method to study sticking of H-atoms from Cu(100).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction of atomic hydrogen, the simplest atom, with transition metal surfaces has attracted large interest, because it is the testing ground for our understanding of surface processes. The simplicity of the adsorbate electronic structure lead to a large body of existing theoretical work on this metal-adsorbate interaction [36][37][38]. The hydrogen metal bond is relatively weak (DHðMe À HÞ < 2 eV for noble metals, and somewhat stronger DHðMe À HÞ % 2 À 3 eV for transition metals [39]).…”
Section: Introductionmentioning
confidence: 99%